CyberGIS-enabled decision support platform for biomass supply chain optimization. (August 2015) - Lin, Tao; Wang, Shaowen; Rodríguez, Luis F.; Hu, Hao; Liu, Yan
Abstract: Biomass supply chain optimization aims to facilitate large-scale production of biofuels by improving the efficiency and effectiveness of biomass feedstock provision. Most existing models are not web based, limited by the accessibility for real-world applications. A CyberGIS-enabled biomass supply chain decision support platform was developed to improve model accessibility and computational performance. The platform includes four major components: BioScope optimization model, GISolve middleware, high-performance cyberinfrastructure, and an interactive web interface. The workflow and functions of each component are provided to illustrate the development and usage of the platform. Case studies and associated system performance have been evaluated to demonstrate the utility of the CyberGIS-enabled decision support platform. Through leveraging cyberinfrastructure resources and interactive web-based interface, the platform enables solving complex biomass supply chain optimization problems. The improved computational performance could provide responsive decision support for group-based applications. Highlights: A CyberGIS-enabled decision support platform was developed for biomass analysis. The platform includes web interface, middleware, model, and cyberinfrastructure. The platform integrates data, modeling and analysis, and result visualization. The platform improves computing performance for complex problem solving.